Ambulatory Blood Pressure Profiles and Correlation with Cardiovascular Risk Factors in a Sample of 390 University Employees in Tanzania - Chuwa G; Chillo P (Dove Medical Press, 2020)
Godfrey Chuwa, Pilly Chillo Department of Internal Medicine, Muhimbili University of Health and Allied Sciences, Dar es Salaam, TanzaniaCorrespondence: Pilly ChilloDepartment of Internal Medicine, Muhimbili University of Health and Allied Sciences, PO BOX 65001, Dar es Salaam, TanzaniaTel +255 22 215 0603Email pchillo2000@yahoo.co.ukBackground: Hypertension is a major risk factor for cardiovascular morbidity and mortality. Increasingly, evidence suggests that 24-hour ambulatory blood pressure (BP) monitoring (ABPM) is more accurate than clinic BP in predicting cardiovascular risk. However, this association has not been widely studied in subSaharan Africa, especially in Tanzania.Aim: To explore the relationship between 24-hour ABPM profiles and cardiovascular risk factors in comparison with clinic BP among Muhimbili University of Health and Allied Sciences (MUHAS) employees.Methods: A descriptive cross-sectional study was conducted from October 2018 to February 2019. Socio-demographic and cardiovascular risk information was gathered. We used an automated ABPM device to record 24-hour ambulatory BP. Correlation between BP profiles and cardiovascular risk factors was done using Pearson’s correlation coefficient, and independent factors for hypertension were determined using logistic regression analysis. P-value of < 0.05 was considered statistically significant.Results: In total, 390 employees participated. Their mean age was 40.5 ± 8.9 years, and 53.6% were men. The mean office systolic and diastolic BP were 126± 12 mmHg and 78± 13 mmHg, respectively, while the corresponding values for mean 24-hour ABPM were 122± 14 and 75± 10 mmHg. The prevalence of hypertension was 23.1%. The prevalence of white coat hypertension was 16.2%, while masked hypertension and nocturnal non-dipping were present in 11.5 and 66.7%, respectively. Overall, the mean 24-hour systolic BP showed the strongest correlations with cardiovascular risk factors while mean office systolic BP showed least. Independent associated factors of hypertension were male gender, age ≥ 40 years, family history of hypertension, central obesity, raised cholesterol and uric acid levels, all p< 0.01.Conclusion: Compared to office BP, ABPM measurements had stronger correlations with cardiovascular risk factors in this population, and therefore likely to reflect true BP. ABPM has revealed high proportion of masked, white coat and nocturnal non-dipping, supporting use of ABPM to detect these clinically important BP profiles.Keywords: ambulatory blood pressure, cardiovascular risk factors, hypertension, white coat hypertension, masked hypertension, nocturnal non-dipping, Tanzania, sub-Saharan Africa